APPLICATION OF PROBLEM SOLVING APPROACH TO INCREASE MATHEMATICAL CRITICAL THINKING SKILL OF GRADE XI-4 STUDENTS OF SMK PASUNDAN 1 BANJARAN ON MATRIX MATERIAL - Eka Noviana Kharisma; M Afrilianto; Euis E Rohaeti (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
This research is the classroon action research. The purpose of this study is to examine the improvement of critical thinking skills mathematically of students class XI-4 SMK Pasundan 1 Banjaran on matrix material through problem solving approach. The problem formulated in thid research whether through problem solving approach, student’s mathematical thinking ability can be improved?. The instrument used in this study is the test of learning outcomes as a test of student’s mathematical critical thinking skills about  matrix material, for preliminary (before action) tests, cycles I and II (after giving the action); and observation sheets fot teachers and students for the conditions of action implementation. The procedure of this study consists of: 1) planning, 2) implemetation of the action, 3) observation and evaluation, and 4) reflection. Based on the results of analysis and discussion, it can be concluded that the critical thinking skills mathematically of students class XI-4 SMK Pasundan 1 Banjaran on matrix material can be improved through problem solving approach